Feature IBM exhibit in the United States pavilion
A demonstration of the IBM 305 RAMAC computer pictured are Dr. Cuthbert C. Hurd, Director of automation research for IBM (left) and Howard S. Cullman, U.S. Commissioner general to the fair description included with photo is in English, French and German.